Bio-inspired design of SiCf-reinforced multi-layered Ti-intermetallic composite. (5th July 2016) - Yu, Wenbo; Zhu, Kai; Aman, Yann; Guo, Zhipeng; Xiong, Shoumei
Abstract: In reference to the well-evolved keratin layer of turtle shell, which has a collagen fiber-reinforced multi-layered structure, bio-mimicking SiCf -reinforced Ti-intermetallic multi-layers were successfully fabricated. The initial Ti and Al foils were firmly bonded to each other through the formed intermetallic layers. Additionally, SiCf and Ti were connected by the compound TiC0.75 formed through the reaction between the Ti matrix and the deposited C coating on SiC fibers. Along the longitudinal direction of SiCf, the ultimate tensile, flexural strengths and fracture toughness of the hybrid composite have been respectively enhanced of 53%, 74% and 75%, while the elongation remained almost similar to the Ti-intermetallic multi-layers composite. In-situ observations indicated that cracks were always initiated in the intermetallic region. The crack propagating paths were significantly changed and the cracks length was visibly prolonged through crack deflection and crack blunting. Due to the strong interfacial connection between the SiC fibers and the Ti matrix, the broken SiCf pieces could strengthen the Ti matrix. Herein, the hybrid composite could support higher external loads than the corresponding Ti–Al intermetallic multilayers without SiCf . Graphical abstract: Highlights: Hybrid composite was designed in reference to turtle keratin. Hybrid composite and corresponding multi-layers composite are compared. Hybrid composite merits the SiCf reinforcement and multilayered crack defection ability.